Multicultural Organizational Culture - Ashri Ramadhani (Denisya Smart Consulting, 2023)
This study examines multiculturalism related to morals in a nation to do something that has become a mutual agreement and then also examines the activities of communication, negotiation, decision making and multicultural teams in a diverse organization. The type of research used in this study is library research with a qualitative approach method. The result of this study is that intercultural communication is a process of conveying messages, information, ideas or feelings between people of different cultural backgrounds. Negotiation is a dynamic and diverse process of interaction and communication, containing art and full of secrets, to achieve a goal of the parties. Intercultural decision making needs to be done because of the difference between expectations or goals and the results achieved. Multiculturalism can simply be understood as an acknowledgment that a country or society is diverse and plural